Challenges in the Elaboration of a Field Interview Instrument to Capture Information for the Evaluation of Adherence to the WHO/PAHO Guiding Principles for Complementary Feeding of the Breastfed Child. Issue 3 (September 2014) - Vossenaar, Marieke; Doak, Colleen M.; Solomons, Noel W.
Background: In 2003, the World Health Organization (WHO) and the Pan American Health Organization (PAHO) published "Guiding principles for complementary feeding of the breastfed child, " which includes a series of 10 recommendations. Objective: To illustrate the challenges in creating operative criteria for the evaluation of concordance with the tenets of the WHO/PAHO Guiding Principles recommendations. Methods: We set out to define operative criteria for the evaluation of adherence to the tenets of the WHO/ PAHO Guiding Principles. The 10 Guiding Principles were divided into subcomponents and examined carefully. Our indicators were based on evaluation variables collected by means of our prospectively designed data collection tool. The 2008 WHO-validated infant and young child feeding (IYCF) indicators were taken as a reference for evaluation. Results: After careful examination of the 10 WHO/ PAHO Guiding Principles, we were able to identify 28 specific subcomponents for evaluation. With our prospectively designed data collection tool, we were able to set evaluations for 17 of these 28 subcomponents. Conclusions: The considerations for devising the criteria involved in evaluation instruments must be transparently available to clarify the interpretations and conclusions derived from their application. Evaluation criteria can be set for most, but not all, IYCF practices of the WHO/PAHO Guiding Principles. Indicators that focus on selected, food-related dimensions of child feeding can be measured in large surveys, whereas other dimensions of optimal feeding, such as hygienic food handling and adequate texture of food, are likely to require more complex measurement and evaluation approaches.